Hydrogen-rich syngas production by reforming of ethanol blended with aqueous urea using a thermodynamic analysis. (1st January 2019) - Wu, Horng-Wen; Lin, Ke-Wei
Abstract: This study presents a new concept of the aqueous urea solution (AUS) to replace pure water and uses a thermodynamic analysis to compare the characteristics of steam and autothermal reforming of ethanol with/without AUS. The results show that hydrogen-rich syngas production under steam reforming of ethanol (SRE) with the blended AUS is higher than that under the pure steam. Under autothermal reforming of ethanol (ATRE), syngas yield increases with an increase in urea, and the thermal neutral temperature (TNT) can be adjusted through the amount of AUS because of the endothermic role of urea in the overall reaction. The best operating condition of ATRE is the H2 O/EtOH equal to 5 and the O2 /EtOH equal to 1.2 at 800 °C, and the reforming efficiency of ethanol with the AUS reaches 93.17% much higher than that without the AUS. The present results are also verified by an experiment and indicate that the use of AUS as a reactant to replace pure steam in ethanol reforming can increase both syngas yield. Highlights: We analyze steam and autothermal reforming of ethanol blended with aqueous urea. Blending ethanol and aqueous urea increases syngas yield and reforming efficiency. For autothermal reforming, a higher added urea reduces thermal neutral temperature. For ethanol blended with aqueous urea, the highest hydrogen yield exists at 750 °C. Reforming efficiency with aqueous urea is 93.17% at H2 O/EtOH of 5, O2 /EtOH of 1.2.